Triple dens invaginatus in a single tooth: Rarest of rare case report - Amandeep Chhina; Kamalpreet Chhina; Nitin Kaushal; Ira Walia (Wolters Kluwer Medknow Publications, 2017)
Dens invaginatus is a rare malformation affecting the teeth. The teeth that are most commonly affected are the permanent maxillary lateral incisors. The mandibular posterior teeth are rarely affected by dens invaginatus. In most of the cases, a single dens invaginatus is seen affecting the tooth. Cases of double dens invaginatus affecting a single tooth are rare, and those of triple dens invaginatus in a single tooth are even rarer. Here, we present a case of a 14-year-old where three dens invaginatus were seen in the mandibular second premolar. This is the fourth case of three dens invaginatus in a single tooth as only three have been reported previously.